Adapting an Evidence-Based HIV Prevention Intervention Targeting High-Risk Migrant Workers: The Process and Outcome of Formative Research - Shrestha, Roman; Karki, Pramila; Pandey, Santosh; Copenhaver, Michael (Frontiers in Public Health, 2016)
Background Historically, HIV prevention efforts in Nepal have primarily focused on heterosexual transmission, particularly, among female sex workers (FSWs) and their male clients, with little acknowledgment of the contribution of migrant workers to the epidemic. The very few HIV prevention efforts that have been attempted with migrants have been unsuccessful primarily due to stigma, discrimination, and insufficient availability of culturally relevant evidence-based interventions (EBIs). As an initial step toward addressing this unmet need, we conducted formative research aimed at adapting an evidence-based HIV risk reduction intervention for implementation among migrants in Nepal. Methods Our formative work involved a critical examination of established EBIs and associated published reports complemented by data elicited through structured interviews with members of the target population and key stakeholders. Between July and August, 2014, we conducted structured one-on-one interview with migrants (n = 5) and key stakeholder (e.g., counselors, field workers, and project coordinator; n = 5), which focused on the HIV risk profiles of the migrants and on ways to optimize intervention content, delivery, and placement within the community-based settings. Data analysis followed a thematic analysis approach utilizing several qualitative data analysis techniques, including inductive analysis, cross-case analysis, and analytical coding of textual data. Results Based on formative research, we adapted the Holistic Health Recovery Program (HHRP), an EBI, to consist of four 30-minute sessions that cover a range of topics relevant to migrants in Nepal. The intervention was adapted with flexibility so that it could be provided in an individual format, implemented within or outside the CBO, and can be delivered in either consecutive or weekly sessions based on time constraints. Conclusions This paper provides a detailed description of the formative research process in preparation for the adaptation of an EBI – taking into account both empirical evidence and input from target population and key stakeholders – for use with migrants in Nepal. We hope, this study will help to inform similar work in the future as a growing number of EBIs have become widely available but may not yet be in optimal form for implementation in real world community-based settings.